Parametric Analysis of Blade Number Influence on the Aerodynamic Performance of a Savonius Rotor - Mohammed Ogab; Muhammad Faris Norazmi; Djamal Hissein Didane (International Journal of Integrated Engineering, 2025)
This study investigates the performance of two-blade and three-blade Savonius rotor wind turbines using computational techniques. The computational fluid dynamics (CFD) simulations are employed using Ansys Fluent as the flow solver while using the hybrid two-equation shear stress transport (SST) as the turbulence model. The performance investigation was based on torque, power and their conversion efficiencies at a ranging tip-speed ratio (TSR) between 0.2 to 1.2. The results of the simulation have been validated with existing work prior to presenting the present results in order to ensure their credibility and accuracy. The results have shown that both models with two-blade and three-blade have shown similar trends for all performance parameters tested. However, the analysis reveals substantial performance disparities between the two configurations. The three-blade design demonstrates superior characteristics, including higher torque values of 0.1077 Nm at TSR 0.8 and 0.434 for the power coefficient, Cp at the same TSR compared to the 2 blades, increased power generation, and improved power coefficients with 0.365 value at the highest TSR compared to the two-blade configuration. The examination of flow distributions has provided valuable insights into flow behavior, highlighting regions of acceleration, deceleration, and stagnation. This study contributes to the existing knowledge by illuminating the performance characteristics of two-blade and three-blade Savonius rotor turbines. The findings serve as a valuable resource for optimizing the design of efficient wind turbine systems, promoting the advancement of renewable energy generation.